Teaching Written Expression According to the Communicative based Approach, Forth Year - Middle School [In Arabic] - Zella, Kamal; Lalaoui, Fatiha (Milev Journal of Research and Studies, 2022)
This research paper aims to stand on the reality of teaching written expression in the fourth year of middle school education where we try to present a descriptive study for the content of this activity according to what was mentioned in the textbook and the curriculum by leading the research toward a survey about the concept of written expression and its relationship to the other Arabic language classroom activities, as well as shedding light on the communicative elements in teaching this activity, the methodology for building its tasks, and the way of evaluation based on the communicative approach. Moreover, The research shows also the addition provided by this specific approach in order to achieve the targeted competency behind teaching written expression.